Matriks Sirkulan dalam Modifikasi Metode Hill Cipher - Sylviani, Sisilia; Fahmi Candra Permana (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2024)
A Circulant matrix is ​​a matrix in which each row shifts one element to the right relative to the previous row vector. In this article, we discuss the use of the circulant matrix in sending and decrypting secret messages using the Hill Cipher method.